Influences of Hot-Air Drying on the Functional Properties of Green Banana Pulp Flour and Its Application in Sponge Cake - Nguyen, Thao Thi Thanh; Tran, Trang Pham Huyen; Vo, Trang Thi Ngoc; Le, An Tran Hoai; Kha, Tuyen Chan (Journal of Technical Education Science, 2025)
Large volumes of by-products generated during food processing are often discarded despite being rich in valuable components such as dietary fiber, antioxidants, and natural functional compounds. In banana starch production, green banana pulp (GBP) represents a fiber-rich residue that can be valorized as a functional flour in bakery applications. This study examined the effects of drying temperatures (50 °C, 60 °C, and 70 °C) and material loads (1.61 kg/m², 2.42 kg/m², and 3.23 kg/m²) on the physicochemical properties of GBP flour and evaluated its partial substitution for wheat flour (10 %, 20 %, and 30 %) in sponge cakes. Drying at 60 °C and 2.42 kg/m² yielded flour with desirable whiteness, the lowest browning index, and maximum soluble sugar retention, while maintaining stable crude fiber content. Incorporating GBP flour increased batter viscosity and crumb firmness but enhanced the dietary fiber content of cakes. The 10% substitution level achieved the most favorable balance between structure, sensory acceptability, and nutritional improvement. Overall, GBP flour is demonstrated as a sustainable, fiber-enriching ingredient that enhances the nutritional profile of sponge cakes while promoting the value-added utilization of agro-industrial by-products and supporting waste reduction in food processing.